Faith, Life, and Multiculturalism in the Thought of Al-Qaradawi: A Study of Al-Īmān wa al-Ḥayāh - Sahidin, Amir; Muslih, Mohammad Kholid; Mochamad Sandisi, Zahratur Rofiqah Binte (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
The issue of faith is the most vital and decisive matter for human beings and must be studied earnestly especially in this modern age of rapid transformation that has brought change to every aspect of human life. In a globalized era marked by a materialistic worldview, faith has weakened and is increasingly absent from human life. Against this backdrop, Sheikh Yusuf al-Qaradawi has made significant efforts to link faith with human existence and to respond to the threats posed by materialism. Through a qualitative content analysis based on library research and the framework of contemporary Islamic theology (‘Ilm al-Kalām al-Jadīd), this study arrives at the following conclusions: First, Sheikh Yusuf al-Qaradawi’s efforts to integrate faith into daily life are evident in his articulation of the essence of faith and its impact on individuals and society. Second, his critique of materialism includes a clarification of the nature of science and an exploration of the relationship between faith and psychological well-being, reason, freedom, and human actions. Third, he emphasized that faith is a fundamental foundation of Islamic humanism